Sexual maturation of schoolchildren with low socio-economic level from Rio Branco-AC - Gil Guerra-Júnior; Carlos Teixeira Ferreira; Wellington Gomes de Carvalho; Edson Farias; Marcel Bahia Lanza (Universidade Federal de Santa Catarina, 2006)
The objective this study was to verify the schoolgirl sexual maturation in a public school from Rio Branco (AC). It was a longitudinal study for 3 consecutive years (2003 to 2005), with the same group of girls who studiedat grades 5 or 6 in a school from Rio Branco (AC). The method proposed by Marshall and Tanner to evaluate beast and pubic. The age of menarche was obtained prospectively. The classification of sexual maturation was done according to Vitalle et al.. The nutritional status was evaluated by bone mass index according to NCHS data and the socioeconomic evaluation, by ABEP (2003) patterns. From 44 schoolgirls who completed the study, 39 (89%) were from middle-lower or lower socio-economic level; and 30 (68%) in 2003 and 21 (48%) were malnourished. In 2003, 35 (79%) had initiated the puberty and only 8 (18%) have presented menarche; while in 2005, 39 (89%) presented advanced or complete stages of sexual development and 37 (84%) menarche. The mean age of menarche was 12.7 + 0.7 years. This sample of girls of a public school from North Region of Brazil showed similar data of menarche in comparison from other national and international studies. The advanced puberty observed in some recent studies was not observed in this sample, probably due to the socio-economic level and the nutritional status without obesity. RESUMO O objetivo deste estudo foi verificar a maturação sexual de escolares do sexo feminino em uma escola pública da cidade de Rio Branco (AC). Trata-se de um estudo longitudinal por três anos consecutivos (2003 a2005), com um grupo de meninas que em 2003 cursavam a 5ª ou 6ª série do Ensino Fundamental II em Rio Branco (AC). O método proposto por Marshall e Tanner para avaliação de mamas e de pêlos pubianos. A idade da menarca foi obtida prospectivamente. A classificação da maturação sexual foi feita de acordo com Vitalle et al. (inserir data). O estado nutricional foi avaliado pelo índice de massa corporal de acordo com o critério do NCHS e a avaliação socioeconômica pelas normas da ABEP (2003). Das 44 meninas que completaram o estudo, 39 (89%) pertenciam ao nível socioeconômico médio-baixo ou pobre; e 30 (68%) em 2003 e 21 (48%) em 2005 estavam desnutridas. Em 2003, 35 (79%) estavam em estadio inicial de desenvolvimento puberal e apenas 8(18%) haviam apresentado menarca, enquanto que em 2005, 39 (89%) estavam em estadio avançado ou completo de desenvolvimento e 37 (84%) apresentavam maturação. A média da idade da menarca foi de 12,7 + 0,7 anos. Conclui-se que esta amostra de meninas de escola pública da região Norte do Brasil, a idade da menarca foi compatível com os dados descritos na literatura nacional e internacional. A antecipação da puberdade descrita em alguns estudos mais recentes, não foi observada, provavelmente, devido ao nível socioeconômico baixo e ao padrão nutricional com a ausência de obesidade.